Robotic versus Laparoscopic Approach in Colonic Resections for Cancer and Benign Diseases: Systematic Review and Meta-Analysis. - Stefano Trastulli; Roberto Cirocchi; Jacopo Desiderio; Andrea Coratti; Salvatore Guarino; Claudio Renzi; Alessia Corsi; Carlo Boselli; Alberto Santoro; Liliana Minelli; Amilcare Parisi (PLoS ONE)
Objectives The aim of this systematic review and meta-analysis is to compare robotic colectomy (RC) with laparoscopic colectomy (LC) in terms of intraoperative and postoperative outcomes. Materials and methods A systematic literature search was performed to retrieve comparative studies of robotic and laparoscopic colectomy. The databases searched were PubMed, Embase and the Cochrane Central Register of Controlled Trials from January 2000 to October 2014. The Odds ratio, Risk difference and Mean difference were used as the summary statistics. Results A total of 12 studies, which included a total of 4,148 patients who had undergone robotic or laparoscopic colectomy, were included and analyzed. RC demonstrated a longer operative time (MD 41.52, P<0.00001) and higher cost (MD 2.42, P<0.00001) than did LC. The time to first flatus passage (MD -0.51, P = 0.003) and the length of hospital stay (MD -0.68, P = 0.01) were significantly shorter after RC. Additionally, the intraoperative blood loss (MD -16.82, P<0.00001) was significantly less in RC. There was also a significantly lower incidence of overall postoperative complications (OR 0.74, P = 0.02) and wound infections (RD -0.02, P = 0.03) after RC. No differences in the postoperative ileus, in the anastomotic leak, or in the conversion to open surgery rate and in the number of harvested lymph nodes outcomes were found between the approaches. Conclusions The present meta-analysis, mainly based on observational studies, suggests that RC is more time-consuming and expensive than laparoscopy but that it results in faster recovery of bowel function, a shorter hospital stay, less blood loss and lower rates of both overall postoperative complications and wound infections.